Establishment of the prokaryotic expression system for OsAFB4 protein in rice - RAN Le; GUO Xiaohao; HUANG Rantao; SHU Qingyao; GUO Fu (浙江大学学报. 农业与生命科学版)
OsAFB4 gene encodes a kind of rice auxin receptor protein, and its deletion can make rice resistant to 2, 4-dichlorophenoxyacetic acid (2, 4-D) and picloram. In order to study its function, characteristics and interaction with auxin herbicides, it is necessary to establish a prokaryotic expression system for OsAFB4 protein. In this study, OsAFB4 gene was cloned into prokaryotic expression vectors pET-32a, pGEX-4T, and pMAL-C6T, respectively. Then, pET-32a-OsAFB4 was transformed into Escherichia coli strain competent cells of OverExpress C43 (DE3), Rosseta2 (DE3) and ER2566, pGEX-4T-OsAFB4 was transformed into E. coli strain competent cells of OverExpress C43 (DE3) and Rosseta2 (DE3), and pMAL-C6T-OsAFB4 was transformed into E. coli strain competent cells of OverExpress C43 (DE3), Rosseta2 (DE3) and TB1. The expression of fusion protein was induced by isopropylthio-β-D-galactoside (IPTG), and the induction conditions were optimized using different induction times, temperatures and IPTG concentrations. The protein gel electrophoresis results indicated that the optimal induction condition for prokaryotic expression of OsAFB4 protein was 200 μmol/L IPTG at 23 ℃ for 12 h. In conclusion, the establishment of the OsAFB4 prokaryotic expression system provides a foundation for research on auxin receptor function and the development of auxin herbicide resistance sites.